The Clinical Relevance and Tumor Promoting Function of C19orf10 in Kidney Renal Clear Cell Carcinoma - Lu, Yanxin; Liao, Ximian; Wang, Tongyu; Hong, Xiaowei; Li, Zesong (Frontiers in Oncology, 2021)
Kidney renal clear cell carcinoma (KIRC) is the most common primary renal neoplasms. Currently, there are few molecular indicators and therapeutic targets that can be used in diagnostic and prognostic assessment. In this study, we identified the C19orf10 expression in KIRC specimens and explored the diagnostic and prognostic value of C19orf10 in KIRC using TCGA and CPTAC database. Loss-of- and gain-of- function of C19orf10 was performed to investigate the roles of C19orf10 on KIRC cell viability, proliferation, migration and invasion via CCK-8, Edu incorporation and Transwell assays respectively. C19orf10 was overexpressed in KIRC tissues and the elevated C19orf10 expression was closely associated with clinicopathological characteristics of KIRC including histological grade, TNM stage, metastatic status. Silencing C19orf10 significantly suppressed the viability, proliferation, migration and invasion ability, while overexpression of C19orf10 promoted the progression and malignant phenotype in KIRC cells. Furthermore, C19orf10 exerted its carcinogenic function by regulating ZO-1 and PTEN/Akt signaling pathway. Moreover, the Kaplan–Meier survival analysis, Cox regression analysis and receiver operating curve analysis showed that patients with C19orf10 overexpression have poor survival time. C19orf10 could discriminate KIRC patients with high-risk from low-risk. Taken together, C19orf10 contributes to KIRC development via ZO-1 and PTEN/Akt signaling pathway and C19orf10 could serve as a potential diagnostic and prognostic candidate and therapeutic target of KIRC.